Genetics of Coxiella burnetii: on the path of specialization. (November 2011) - Minnick, Michael F; Raghavan, Rahul
Coxiella burnetii is an extremely infectious, zoonotic agent that causes Q fever in humans. With the exception of New Zealand, the bacterium is distributed worldwide. Coxiella is classified as a select agent based on its past and potential use as a bioweapon and its threat to public health. Despite decades of research, we know relatively little regarding Coxiella ''s molecular pathogenesis, and a vaccine is not widely available. This article briefly reviews the unusual genetics of C. burnetii ; a pathogen that retains telltale genetic mementos collected over the course of its evolutionary path from a free-living bacterium to an obligate intracellular parasite of eukaryotic host cell phagosomes. Understanding why these genetic elements are maintained may help us better understand the biology of this fascinating pathogen.